Classroom discipline patterns prevalent among sixth- grade learners "A field study among a sample of teachers of the first cycle of basic education in the schools of the city of Latakia (Journal of Hama University, 2023)
The research aims to identify the prevailing patterns of classroom discipline among sixth-grade learners from the point of view of their teachers, and to identify the differences in the estimates of the sample members on the patterns of classroom discipline prevailing among sixth-grade learners according to the variable (academic qualification, years of experience), and in order to achieve the objectives of the research. The descriptive approach was used through the design of a questionnaire consisting of (23) items, which was distributed to (200) male and female teachers of the first cycle of basic education in the city of Lattakia, The study reached the following results: The patterns of classroom discipline prevailing among sixth-grade learners from the point of view of the teachers came with a high degree, and self-discipline ranked first with an arithmetic mean (3.85) and a high degree of approval, then preventive discipline with an arithmetic mean (3.81) and a high degree of approval, then analytical discipline with an arithmetic mean (3.81) and a high degree of approval, It was also found that there were no differences between the teachers’ responses to the questionnaire of the prevailing classroom discipline patterns among sixth-grade learners according to the variables of educational qualification and number of years of experience. Discipline and the need to adhere to it, and to follow positive strategies that motivate students to self-commit to the teacher's instructions.
Keywords: Classroom discipline, Sixth-grade learners